SECURITY SERVICE OF UKRAINE WITHIN SECURITY AND DEFENSE SECTOR OF UKRAINE (Law and Safety, 2018)
One of the main subjects of guaranteeing security and defense of Ukraine – the Security Service of Ukraine (SSU) – has been considered in the historical perspective and in modern conditions.The main tasks and powers of this law-enforcement agency of special purpose at the present stage of the establishment of the state, in the conditions of aggression of the Russian Federation in the East of Ukraine and the temporary occupation of the territory of the Autonomous Republic of Crimea have been characterized.The author has emphasized the necessity of reforming the SSU. Based on the requirements of the Laws of Ukraine “On the Security Service of Ukraine”, “On the Fundamentals of National Security of Ukraine”, the National Security Strategy of Ukraine and the Concept of Developing the Security and Defense Sector of Ukraine, the author has set out the tasks, the accomplishment of which will reflect the reform of the Service, as well as successive tasks that are generally make it possible for the Security Service of Ukraine to fulfill the current tasks of ensuring national security.
Keywords: security, defense, Security Service of Ukraine, security sector, state.